Association between mood episode severity and c-reactive protein levels in bipolar disorder: an exploratory cross-sectional study - Juhi Gupta; Dipesh Bhagabati (International Journal Of Community Medicine And Public Health, 2026)
Background: Bipolar disorder is a chronic, recurrent mood disorder associated with significant disability, functional impairment, and medical comorbidities. Increasing evidence suggests that immune-inflammatory mechanisms contribute to its pathophysiology. C-reactive protein (CRP), a widely used biomarker of systemic inflammation, has been reported to be elevated in bipolar disorder, particularly during manic episodes. However, data from the Indian population examining the association between CRP levels and severity of mood episodes using standardized rating scales remain limited. Therefore, this study was conducted to evaluate the association between severity of manic and depressive episodes and serum CRP levels in patients with bipolar disorder. Methods: This hospital-based cross-sectional analytical study was conducted at a tertiary care center. Thirty patients diagnosed with bipolar disorder were assessed during either a manic episode (n=15) or a depressive episode (n=15). Severity was evaluated using the young mania rating scale (YMRS) and Hamilton depression rating scale (HAM-D). Serum CRP levels were measured and categorized as normal (≤5 mg/l) or elevated (>5 mg/l). Correlations were analysed using Pearson’s correlation coefficient. Results: Fourteen participants (46.7%) had elevated CRP levels. Mean CRP levels were higher in manic episodes (17.82±16.38 mg/l) than depressive episodes (9.80±8.14 mg/l). A significant positive correlation was found between YMRS scores and CRP levels (r=0.5622, p=0.0292), whereas no significant correlation was observed between HAM-D scores and CRP levels (r=−0.1672, p=0.5515). Conclusions: Severity of manic symptoms is positively associated with systemic inflammation, supporting inflammation as a state-dependent correlate of mania.